2015
DOI: 10.1111/jcpp.12464
|View full text |Cite
|
Sign up to set email alerts
|

Identifying mechanisms that underlie links between COMT genotype and aggression in male adolescents with ADHD

Abstract: BackgroundThere is a known strong genetic contribution to aggression in those with ADHD. In a previous investigation of a large population cohort, impaired ‘emotional/social cognitive’ processing, assessed by questionnaire, was observed to mediate the link between COMT Val158Met and aggression in individuals with ADHD. We set out to replicate and extend this finding in a clinical sample, using task‐based and physiological assessments of emotional and cognitive processing. Our aim was to test the hypothesis tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 35 publications
2
29
0
Order By: Relevance
“…Our results show that the affective response was significantly smaller for high‐risk children, in particular in response to seeing someone else in pain or fear. Problems in affective empathy in children with CD (Van Goozen et al., ) or psychopathic traits in response to negative emotions have been observed before (Lockwood, Bird, Bridge, & Viding, ). However, we observed similar deficits in children who are not psychopathic and also do not have a diagnosis of CD, showing that these affective processes could play a role in a much larger range of problem behaviours.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Our results show that the affective response was significantly smaller for high‐risk children, in particular in response to seeing someone else in pain or fear. Problems in affective empathy in children with CD (Van Goozen et al., ) or psychopathic traits in response to negative emotions have been observed before (Lockwood, Bird, Bridge, & Viding, ). However, we observed similar deficits in children who are not psychopathic and also do not have a diagnosis of CD, showing that these affective processes could play a role in a much larger range of problem behaviours.…”
Section: Discussionmentioning
confidence: 78%
“…Bartoli & Wendt, 2014;Blair, 2005;Bons et al, 2013;Dadds, El Masry, Wimalaweera, & Guastella, 2008;De Vignemont & Singer, 2006;Lovett & Sheffield, 2007;Singer, 2006). Several studies have examined both affective and cognitive empathy in children with antisocial behaviour and found impaired affective empathy but unimpaired cognitive empathy in children with conduct disorder and high levels of callous-unemotional (CU) traits (Anastassiou-Hadjicharalambous & Warden, 2008;Schwenck et al, 2012), in children with conduct disorder with or without ADHD (Van Goozen et al, 2016), in those with conduct problems and high levels of CU-traits (Pasalich, Dadds, & Hawes, 2014) and in children with psychopathic tendencies or conduct problems recruited from the community (Jones, Happ e, Gilbert, Burnett, & Viding, 2010), in line with the empathy imbalance theory of Smith (2009Smith ( , 2010. In addition, studies that examined only cognitive empathy showed normal cognitive empathy (Sutton, Reeves, & Keogh, 2000;Woodworth & Waschbusch, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…To evaluate empathic responses, corresponding here to emotional recognition, we used an explicit empathy test, according to the standards of previous studies presenting dynamic stimuli (van Goozen et al, 2016;Hubble et al, 2017). Participants were asked to identify the emotional context in each video and their responses were scored on the basis of three components: (1) Recognizing the most important emotion in the actress: this component has been considered as cognitive empathic response (van Goozen et al, 2016). If the participant identified the main emotion more intensely than other emotions on the list, they received three points.…”
Section: Empathic Responses Emotional Measures and Eye-movement Recmentioning
confidence: 99%
“…In this line, we have not found studies that examine the influence of both, empathy trait and gender, on the empathic process using dynamic stimuli in typical population. Although some studies have evaluated the empathic process using dynamic stimulus and recorded eye movements in clinical populations (van Rijn et al, 2014;van Goozen et al, 2016;Hubble et al, 2017;van Zonneveld et al, 2017), they did not determine the influence of empathy trait or gender. As far as we know, only one study has included typical adult population, empathy trait, and dynamic stimuli (video) to compare neutral and sad emotions (Cowan et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This theory, also proposed by Shelley-Tremblay and Rosen (17), suggests that ADHD-associated aggression (19)(20)(21) may have been advantageous for fighting and warfare in a potential "genocidal" war between Homo Sapiens and the Neanderthals.…”
Section: The Fighter Theorymentioning
confidence: 82%